RELATIONSHIP BETWEEN PATTERN OF STUDY AND CREATIVITY ON STUDENTS’ ACADEMIC ACHIEVEMENT IN BORNO STATE COLLEGE OF EDUCATION: IMPLICATIONS FOR COUNSELLING - Goni, U.; Salawu, A. A. (Sokoto Educational Review, 2018)
This is a correlational study designed to determine the relationship between pattern of study and creativity on students’ academic achievement in Colleges of Education in Borno State. The study set two research objectives and tested two research hypotheses. It used conceptual framework and cognitive approaches; this study is unique because Njidda (1994) investigated the relationship between study habits and performance of Diploma students in Faculty of Education University of Maiduguri while this study investigated the relationship between pattern of study and creativity on students’ academic achievement in Borno State College of Education. The target population fo r this study was 4,517 students who have registered in NCE awarding institutions in Borno State. Purposive sampling technique was used to select two Colleges of Education in Borno State, the stratified random sampling procedure was also employed to select (322) participants 186 students from 351NCE III students’ from Kashim Ibrahim College of Education, Maiduguri and 136 students from 210 NCE III students from Umar Ibn Ibrahim College of Education, Science and Technology, Bama. Students’ Pattern of Study Inventory (SPSI) and Students’ Creativity Test (SCT) was used by the researchers. Pearson’s r was used to test the hypotheses raised in this study. The results indicated that there is very low and positive relationship between creativity and patterns of study among students of Colleges of Education and indicated a high and positive relationship between the two variables. Based on the results the study recommended for College of Education counsellors to give more encouragement to the students to improve their pattern of study and use of some designed study time tables to improve outcome o f their studies. There is also the need for r College counsellors to give advice to the students to sustain their effort since the results revealed high and significant relationship between students ’pattern of study and creativity.